J.W. Rangellin hallituksen keskeiset ministerit Tarvaspäässä
sisällön kuvaus: edessä vasemmalta: tuntematon, L.A. Puntila, Toivo Horelli, Oskari Lehtonen, Rolf Witting, J.W. Rangell ja Pauli Soisalo
Keywords: huvilat; tornit; miesten puvut; Horelli, Toivo; Lehtonen, Oskari; Puntila, L. A; Rangell, J. W; Soisalo, Pauli; Witting, Rolf; Suomen entinen kunta/pitäjä, Espoo, Tarvaspää, Espoo, Tarvaspää